2019
DOI: 10.4018/ijgbl.2019040101
|View full text |Cite
|
Sign up to set email alerts
|

Students' Acceptance of Gamification in Higher Education

Abstract: Gamification provides a practical approach to improving learning processes, especially the learner's motivation. However, little research has been conducted on student intentions to use gamification in higher education. Therefore, this study explored the gamification in higher educational courses by collecting surveys and discusses the factors influencing the acceptance of gamification in higher education. Based on the PLS-SEM results, students should take initial game-based learning content to be more familia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0
6

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 27 publications
2
34
0
6
Order By: Relevance
“…Scholars have revealed that social factors are a strong determinant of user intentions towards gamified services (C. H. Chung, Shen, & Qiu, 2019;Hamari & Koivisto, 2015). Moreover, FC is a significant factor influencing students to accept gamification (C. H. Chung et al, 2019). Game dynamics and mechanics affect the development of a habit through the mobile application.…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…Scholars have revealed that social factors are a strong determinant of user intentions towards gamified services (C. H. Chung, Shen, & Qiu, 2019;Hamari & Koivisto, 2015). Moreover, FC is a significant factor influencing students to accept gamification (C. H. Chung et al, 2019). Game dynamics and mechanics affect the development of a habit through the mobile application.…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…British Journal of Educational Technology Vol 52 No 1 2021 points, badges and role-play are common gamification elements of current gamified e-learning platforms/systems/applications (Kapp, 2012). A number of researchers have looked into the effects of gamification in learning, such as increasing learners' engagement, stimulating learning motivation, changing learners' learning attitudes and behaviors, and improving academic performance and competence (Buckley & Doyle, 2016;Chung, Shen, & Qiu, 2019;Huang, Hew, & Lo, 2018). The effectiveness of gamification in learning is due to the premise that students can gain fun from gamified learning content, environments, and activities, leading to increased motivation and improved learning behaviors (Buckley & Doyle, 2016).…”
mentioning
confidence: 99%
“…Gamification is a wellknown technique in education, organization engagement, crowdsourcing, commerce, information retrieval, and so on [34,35]. It is practical to improve learning processes especially the learners' motivation [36]. Gamification techniques are benefiting from advances in ICT.…”
Section: Gamification and Serious Gamesmentioning
confidence: 99%